2019
DOI: 10.1124/jpet.118.254128
|View full text |Cite
|
Sign up to set email alerts
|

Colony-Stimulating Factor-1 Antibody Lacnotuzumab in a Phase 1 Healthy Volunteer Study and Mechanistic Investigation of Safety Outcomes

Abstract: The colony-stimulating factor-1 (CSF-1) receptor pathway has been implicated in a variety of diseases, and CSF-1-dependent mechanisms are also involved in bloodborne protein clearance.Lacnotuzumab is a novel, high-affinity, humanized, anti-CSF-1 monoclonal antibody that prevents CSF-1 mediated receptor activation. This phase 1, two-part, double-blind study in healthy volunteers assessed the safety and tolerability of lacnotuzumab and its pharmacokinetics (PK) and pharmacodynamic properties. Part A (n = 36) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
2
13
1
Order By: Relevance
“…Similarly, deletions or truncations of the 3′ UTR of CCND1 have been reported to lead to cyclin D1 overexpression in mantle cell lymphoma via deletion of miRNA target sites . It is thus likely that CSF1 alterations removing this region would likewise result in decreased mRNA degradation in tenosynovial giant cell tumors and increased levels of functional CSF1 cytokine‐mediated activation of monocyte‐macrophage CSF1R, explaining the recent success of therapies targeting the CSF1‐CSF1R axis in this disease …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, deletions or truncations of the 3′ UTR of CCND1 have been reported to lead to cyclin D1 overexpression in mantle cell lymphoma via deletion of miRNA target sites . It is thus likely that CSF1 alterations removing this region would likewise result in decreased mRNA degradation in tenosynovial giant cell tumors and increased levels of functional CSF1 cytokine‐mediated activation of monocyte‐macrophage CSF1R, explaining the recent success of therapies targeting the CSF1‐CSF1R axis in this disease …”
Section: Discussionmentioning
confidence: 99%
“…45,46 It is thus likely that CSF1 alterations removing this region would likewise result in decreased mRNA degradation in tenosynovial giant cell tumors and increased levels of functional CSF1 cytokine-mediated activation of monocyte-macrophage CSF1R, explaining the recent success of therapies targeting the CSF1-CSF1R axis in this disease. [9][10][11][12]32 Earlier studies of tenosynovial giant cell tumors suggested that promoter swapping with COL6A3 led to CSF1 upregulation via transcriptional control under the strong collagen promoter, analogous to the mechanism of PDGFB overexpression when fused to the COL1A1 promoter in dermatofibrosarcoma protuberans. 47 Quite recently, CBL mutations were identified in 35% of tenosynovial giant cell tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This new class of immune‐modulatory drugs has been recently incorporated in the treatment armamentarium of advanced malignant neoplasms, but also in several inflammatory conditions in which aberrant CSF1 signaling has been proved 7 . Despite all patients receiving the combination of anti‐CSF1R and anti‐PD‐L1 mAb, we consider the CSF1 pathway blockade as the cause of the observed effects, because cutaneous mucin deposits have been observed in monkeys treated with anti‐CSF1R, 8 and conversely no cases of dermal mucinosis had been published insofar as anti‐programmed death 1 or PD‐L1 therapies 9 . Notably, one of our patients presented a distinct mild lichenoid cutaneous eruption secondary to anti‐PD‐L1 treatment, previous to cutaneous mucinosis.…”
Section: Discussionmentioning
confidence: 99%